(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the mesial-distal positioning of the maxillary first permanent molar in children who present with ectopic eruption of the maxillary first permanent molar (PFMEE). Methods: panoramic radiographs and lateral cephalometric radiographs 12 children of both genders were evaluated. The study group was composed of 12 children with PFMEE and the control group was composed of 12 children with normal occlusion with the first upper permanent molar in occlusion. After selecting the exams from both groups and performing the anatomical tracings, linear and angular measurements were performed. In the lateral cephalometric radiographs the following angles were evaluated: SNGo.GN, SN.GN, SNA, SNB, ANB, 6mx.Palatal Plane and the 6mx.PTV distance. In the panoramic radiograph the angles 6mx.Infraorbital Plane and 6mx.Occlusal Plane were evaluated. Results: PFMEE can occur in individuals regardless of their skeletal pattern. The control group showed much greater angular measurements 6mx.Palatal Plane and 6mx.Infraorbital Plane. Conclusion: There is no relationship between PFMEE and craniofacial growth pattern, there is no direct relationship with the anteroposterior relationship of the apical bases and in cases of PFMEE the mesial angulation is reduced, representing lack of space for eruption of the first permanent molars.